PERLINDUNGAN HUKUM TERHADAP PEMENANG LELANG EKSEKUSI HAK TANGGUNGAN DALAM PENGUASAAN OBJEK LELANG - Hermawan Tri Prasetyo (Journal of Law ( Jurnal Ilmu Hukum ), 2020)
ABSTRACT  Problems that occur related to the mastery of the auction object that the auction winner execution right tangungan not always able to master the auction object.This type of research used in writing this thesis is normative juridical research with a statutory approach and a conceptual approachThe results showed that the form of legal protection for auction winners was preventive and repressive as regulated in Vendureglement, PMK Number 27 / PMK.06 / 2016, HIR, Jurisprudence of the Supreme Court Decision, but all of these did not fully provide legal protection for auction winners. While the factors that cause the object of auction cannot be controlled by the auction winner is a court ruling stating that the auction of mortgage rights is null and void by law and there are residents of the auction object who do not want to leave the auction object because they are owners, heirs, and tenants. If this happens, the efforts made in accordance with applicable regulations are to demand compensation from the seller and the submission of forced emptying to the local District Court. Keywords: Legal Protection, Execution Auction, Mortgage Rights